Transaction Management techniques and practices in current cloud computing environment: a survey - Waqas, Ahmad; Mahessar, Abdul Waheed; Mahmood, Nadeem; Bhatti, Zeeshan; Karbasi, Mostafa; Shah, Asadullah (AIRCC Publishing Corporation, 2015)
Distributed database management systems (DBMSs)have limited capacity to manage overhead of distributed transactions due to certain failures. These types of failures don't guarantee the enforcement of transactional properties and which reduces the scalability and availability of these systems. Research in this area proved that scaling out whiling providing consistency of transactions and guaranteeing availability is the presence of different failures in distributed computing environment is not feasible. As a result, the database community have used vertical scaling rather than horizontal scaling. Moreover changes in data access patterns resulting from new generation of web applications with high scalability and availability guarantees weaker consistency. In this paper we have analyses that how different systems such as ElasTras, Mstore, Sinfonia, ecStore and Gstore provide scalable transactional data access in cloud computing environment. We have also discussed transactions management (TM) in Gstore in detail and compared with other techniques and protocols used in current cloud based systems.